A case study of records management practices in historic motor sport - Joseph, Pauline (Emerald Group Publishing Limited, 2016)
Purpose: This paper aims to report on empirical research that investigated the records management practices of two motor sport community-based organisations in Australia. Design/methodology/approach: This multi-method case study was conducted on the regulator of motor sport, the Confederation of Australian Motor Sport Ltd (CAMS) and one affiliated historic car club, the Vintage Sports Car Club (VSCC), in Western Australia. Data were gathered using an online audit tool and by interviewing selected stakeholders in these organisations about their organisation’s records management practices. Findings: The findings confirm that these organisations experience significant information management challenges, including difficulty in capturing, organising, managing, searching, accessing and preserving their records and archives. Hence, highlighting their inability to manage records advocated in the best practice Standard ISO 15489. It reveals the assumption of records management roles by unskilled members of the group. It emphasises that community-based organisations require assistance in managing their information management assets. Research limitations/implications: This research focused on the historic car clubs; hence, it did not include other Australian car clubs in motor sport. Although four historical car clubs, one in each Australian state, were invited to participate, only the VSCC participated. This reduced the sample size to only one CAMS-affiliated historical car club in the study. Hence, further research is required to investigate the records management practices of other CAMS affiliated car clubs in all race disciplines and to confirm whether they experienced similar information management challenges. Comments from key informants in this project indicated that this is likely the case. Practical implications: The research highlights risks to the motor sport community’s records and archives. It signals that without leadership by the sport’s governing body, current records and community archives of CAMS and its affiliated car clubs are in danger of being inaccessible, hence lost. Social implications: The research highlights the risks in preserving the continuing memory of records and archives in leisure-based community organisations and showcases the threats in preserving its cultural identity and history. Originality/value: It is the first study examining records management practices in the serious leisure sector using the motor sport community.